Regeneration of Articular Cartilage Using Membranes of Polyester Scaffolds in a Rabbit Model - Maciej Baranowski; Monika Wasyłeczko; Anna Kosowska; Andrzej Plichta; Sebastian Kowalczyk; Andrzej Chwojnowski; Wojciech Bielecki; Jarosław Czubak (MDPI AG, 2022)
One promising method for cartilage regeneration involves combining known methods, such as the microfracture technique with biomaterials, e.g., scaffolds (membranes). The most important feature of such implants is their appropriate rate of biodegradation, without the production of toxic metabolites. This study presents work on two different membranes made of polyester (L-lactide-co-ε-caprolactone-PLCA) named "PVP and "Z". The difference between them was the use of different pore precursors-polyvinylpyrrolidone in the "PVP" scaffold and gelatin in the "Z" scaffold. These were implemented in the articular cartilage defects of rabbit knee joints (defects were created for the purpose of the study). After 8, 16, and 24 weeks of observation, and the subsequent termination of the animals, histopathology and gel permeation chromatography (GPC) examinations were performed. Statistical analysis proved that the membranes support the regeneration process. GPC testing proved that the biodegradation process is progressing exponentially, causing the membranes to degrade at the appropriate time. The surgical technique we used meets all the requirements without causing the membrane to migrate after implantation. The "PVP" membrane is better due to the fact that after 24 weeks of observation there was a statistical trend for higher histological ratings. It is also better because it is easier to implant due to its lower fragility then membrane "Z". We conclude that the selected membranes seem to support the regeneration of articular cartilage in the rabbit model.